Analisis Berpikir Reversible Siswa SMP dalam Menyelesaikan Masalah Statistika - Syarifatul Maf'ulah; Jauhara Dian Nurul Iffah; Mochamad Nur Hasan; Ilmi Auliya Rahma (Universitas PGRI Adi Buana Surabaya, 2023)
Reversible thinking is a type of mental activity that has an important role in a person's success in solving problems. Problem solving is the heart of learning mathematics. Reversible thinking must be developed so that students have good problem solving skills. The purpose of this research is to describe the back-and-forth thinking of junior high school students in solving statistical problems. This type of research is descriptive qualitative with instrument tests. The research subjects were class VII students of SMPN 1 Gudo Jombang. Data collection by giving a test in one class VII SMPN 1 Gudo as many as 33 students. Next, one student who has the highest score is selected to be analyzed more deeply regarding his reversible thinking. The results of the study were that 78.9% of students were able to complete the first question, which was a question where the answer could be directly determined (data was known, the average was asked), but only 45.5% and 30.3% of students were able to complete the next two questions respectively. , which in solving it requires reversible thinking. The next two problems are problems that are the opposite of the first problem. Based on the test results, one student was selected with the highest test score, namely AAN. AAN is able to solve all problems correctly, both from the aspect of the settlement procedure and the final result. AAN has involved aspects of reversible thinking well in solving statistical problems. Among these aspects are forward, backward, and reverse aspects.